The Role Of Financial System Indicators In Supporting Economic Development In Syria - شرف, سمير; الصائغ, وجد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The financial system plays an important role in the economies of countries, Because of its overlap and interdependence with many variables of economic activity. Thus, an efficient financial system enhances economic and financial stability, and promotes investment and growth. The financial system is the main instrument for financing economic development, by directing surplus funds to channels that serve the financial preference of the state, so this research aims to identify the extent of the financial system in Syria's contribution to supporting the process of economic development. The research relied on the descriptive analytical approach, by considering the GDP as a dependent variable, and the rest of the financial system variables as independent variables (bank credit, public expenditures, investment), The "inflation rate" and "political stability index" variables were entered as "control" variables, for a period between (2004-2017). The measurement was done by finding the multiple regression equation, using the SPSS program to extract the data. The research reached the conclusion that: The financial system affects on economic development in Syria, Where bank credit affects positively on GDP, This is offset by a higher rate of growth in the volume of public expenditures than in the rate of growth of the gross domestic product, as well as a weak investment contribution to GDP during The study period.